The regulatory climate in the government and private kindergarten children (Comparative Study) - الطاف ياسين خضر ايناس مالك اسماعيل (College of Education for Women, 2019)
The research problem boils question is there in Riyadh organizational climate that enables them to do their work properly and whether there are differences between the government and private Riyadh depending on the organizational climate has sought Find measure: 1 regulatory climate for kindergarten 2. The difference between government and private Riyadh depending on the organizational climate. Limited research on the (200) parameter of the Riyadh government and private parameters for the year (20,142,015) In order to achieve the research objectives the researchers built a regulatory climate in accordance with the scientific steps to build a psychological scales measure After the formulation of climate regulation paragraphs of the (30) paragraph has been confirmed the veracity of standards-mediated presentation to the A group of experts has been shown expire after making some amendments bringing the number of paragraphs (28) and alternatives (agree, AC, I do not agree), paragraph, and then applied to the sample research found the following results: 1 no good regulatory climate in Riyadh in general 2. There statistically significant differences between the government and private Riyadh in the regulatory climate and in favor of civil Riyadh differences